Ketoconazole inhibits Malassezia furfur morphogenesis in vitro under filamentation optimized conditions - Sirida Youngchim (2018)
ï¿½ 2016, Springer-Verlag Berlin Heidelberg. Malassezia furfur, a constituent of the normal human skin flora, is an etiological agent of pityriasis versicolor, which represents one of the most common human skin diseases. Under certain conditions, both exogenous and endogenous, the fungus can transition from a yeast form to a pathogenic mycelial form. To develop a standardized medium for reproducible production of the mycelial form of M. furfur to develop and optimize susceptibility testing for this pathogen, we examined and characterized variables, including kojic acid and glycine concentration, agar percentage, and pH, to generate a chemically defined minimal medium on which specific inoculums of M. furfur generated the most robust filamentation. Next, we examined the capacity of ketoconazole to inhibit the formation of M. furfur mycelial form. Both low and high, 0.01, 0.05 and 0.1ï¿½ï¿½g/ml concentrations of ketoconazole significantly inhibited filamentation at 11.9, 54.5 and 86.7%, respectively. Although ketoconazole can have a direct antifungal effect on both M. furfur yeast and mycelial cells, ketoconazole also has a dramatic impact on suppressing morphogenesis. Since mycelia typified the pathogenic form of Malassezia infection, the capacity of ketoconazole to block morphogenesis may represent an additional important effect of the antifungal.